Boosting Repurchase Intentions: The Influence of Service, Quality, and Customization for Shopee Zerone Japan Users in Surabaya - Christian Calvin Anggriawan; Yolanda Soedibyo (Universitas Pelita Harapan, 2024)
The current trend in vehicle maintenance focuses on keeping the appearance and performance of vehicles optimal by utilizing technology and environmentally friendly products. Modern consumers prioritize convenience, efficiency, and sustainability, including the use of applications for tracking vehicle conditions and scheduling regular services at official workshops. Maintenance products that support fuel efficiency and eco-friendly oils are also increasingly favored. Zerone Japan is a brand that provides a variety of automotive care needs for vehicle enthusiasts. This research aims to determine the influence of Information Quality, Service Quality, Preferential Treatment, and Customization on Repurchase Intention through Perceived Value. The expected benefit of this research is to expand knowledge in the field of management, particularly regarding the influence of these variables. The research is causal in nature, using a quantitative method and AMOS 24.0 software to process primary data from 150 Shopee Zerone Japan application consumers in Surabaya, gathered through the Snowball Sampling technique. The respondents are men and women, aged 18-60, residing in Surabaya, and have made purchases through the Shopee Zerone Japan app at least twice in the last six months. In this study, all variables, including Perceived Value, Information Quality, Service Quality, Preferential Treatment, and Customization, have a positive and significant effect on Repurchase Intention.